2009
DOI: 10.1101/lm.918309
|View full text |Cite
|
Sign up to set email alerts
|

Sex influences on the neurobiology of learning and memory

Abstract: In essentially every domain of neuroscience, the generally implicit assumption that few, if any, meaningful differences exist between male and female brain function is being challenged. Here we address how this development is influencing studies of the neurobiology of learning and memory. While it has been commonly held that males show an advantage on spatial tasks, and females on verbal tasks, there is increasing evidence that sex differences are more widespread than previously supposed. Differing performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
400
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 610 publications
(459 citation statements)
references
References 258 publications
(397 reference statements)
38
400
3
3
Order By: Relevance
“…Although the exact mechanisms for these differences are unknown, several potential differences have been found in brain structure (reviewed in Andreano and Cahill 2009). It has been demonstrated that women have greater volume in memory-related areas including the hippocampus (Filipek et al, 1994), caudate nucleus (Filipek et al, 1994;Murphy et al, 1996), anterior cingulate gyrus (Paus et al, 1996), and dorsolateral prefrontal cortex (Schlaepfer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms for these differences are unknown, several potential differences have been found in brain structure (reviewed in Andreano and Cahill 2009). It has been demonstrated that women have greater volume in memory-related areas including the hippocampus (Filipek et al, 1994), caudate nucleus (Filipek et al, 1994;Murphy et al, 1996), anterior cingulate gyrus (Paus et al, 1996), and dorsolateral prefrontal cortex (Schlaepfer et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The second baseline condition consisted of an odd-even number judgment task. This second baseline was included because it has been shown that 1 The current dataset only included women, as there is evidence that AM (Andreano & Cahill, 2009), and possibly ToM (Baron-Cohen et al, 1997), differ across sex. Although beyond the scope of the current study, sex differences in brain networks underlying AM and ToM is an important topic for future research.…”
Section: Stimulimentioning
confidence: 99%
“…This more efficient performance is characterized by visiting less non-relevant pages, using the back-button less often and lower experiences of feeling lost (Ahmed & Blustein, 2005). For gender differences in learning, memory and spatial ability see Andreano and Cahill (2009).…”
Section: Navigating In Hypertextmentioning
confidence: 99%